Gross-Morphological Studies on Placenta and Fetal Cotyledons of Gir Cows and Jaffrabadi Buffaloes - Padodara, Ramesh J. (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted to compare the gross parameters of the placenta and their characteristics between Gir cows and Jaffrabadi buffaloes. It has shown that there is a great variation in weight, cotyledon numbers, and diameter of the cotyledon of placenta in Gir cow and Jaffrabadi buffalo. Parameters like calf weight, placental weight, numbers and size of cotyledons are found significantly higher in Jaffrabadi buffaloes than Gir cows. Morphologically, fetal cotyledons are convex-shaped and with distinct caruncular stalk (pendunculated) in Gir cow whereas convex and non-pendunculated in Jaffrabadi buffaloes.